Numerical simulations of an ocean-continent convergent system: Influence of subduction geometry and mantle wedge hydration on crustal recycling - Roda, M.; Marotta, A. M.; Spalla, M. I. (Geochemistry, geophysics, geosystems : G3, 2010)
The effects of the hydration mechanism on continental crust recycling are analyzed through a 2‐D finite element thermomechanical model. Oceanic slab dehydration and consequent mantle wedge hydration are implemented using a dynamic method. Hydration is accomplished by lawsonite and serpentine breakdown; topography is treated as a free surface. Subduction rates of 1, 3, 5, 7.5, and 10 cm/yr; slab angles of 30°, 45°, and 60°; and a mantle rheology represented by dry dunite and dry olivine flow laws have been taken into account during successive numerical experiments. Model predictions pointed out that a direct relationship exists between mantle rheology and the amount of recycled crustal material: the larger the viscosity contrast between hydrated and dry mantle, the larger the percentage of recycled material into the mantle wedge. Slab dip variation has a moderate impact on the recycling. Metamorphic evolution of recycled material is influenced by subduction style. TPmax, generally representative of eclogite facies conditions, is sensitive to changes in slab dip. A direct relationship between subduction rate and exhumation rate results for different slab dips; this relationship does not depend on the used mantle flow law. Thermal regimes predicted by different numerical models are compared to PT paths followed by continental crustal slices involved in ancient and recent subduction zones, making ablative subduction a suitable precollisional mechanism for burial and exhumation of continental crust.